2014
DOI: 10.1002/ijop.12126
|View full text |Cite
|
Sign up to set email alerts
|

Values for gender roles and relations among high school and non‐high school adolescents in a Maya community in Chiapas, Mexico

Abstract: In the current study, I describe values for gender roles and cross-sex relations among adolescents growing up in a southern Mexican Maya community in which high school was introduced in 1999. A total of 80 adolescent girls and boys, half of whom were attending the new high school, provided their opinions on two ethnographically derived vignettes that depicted changes in gender roles and relations occurring in their community. Systematic coding revealed that adolescents not enrolled in high school tended to pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…However, the design of these two studies does not enable us to explore the role of individual sociodemographic factors. However, other studies in this special section do (Manago, 2015;Maynard, Greenfield, & Childs, 2015;Weinstock, 2015;Zeng & Greenfield, 2015).…”
Section: Limitationmentioning
confidence: 88%
“…However, the design of these two studies does not enable us to explore the role of individual sociodemographic factors. However, other studies in this special section do (Manago, 2015;Maynard, Greenfield, & Childs, 2015;Weinstock, 2015;Zeng & Greenfield, 2015).…”
Section: Limitationmentioning
confidence: 88%
“…There were no gender differences in value priorities; however, in a more detailed analysis of two vignettes that focused on gender roles and mix‐sex relations, Manago () found that beliefs about benefits and risks of various aspects of gender egalitarianism did differ by gender. Girls more often described benefits of self‐expression in gender roles, but risks in terms of mixed sex relations.…”
Section: Gender and Education In Zinacantánmentioning
confidence: 99%
“…The results, in general, supported Greenfield's theory. As the societies moved from Gemeinschaft to Gesellschaft, individuals tended to become more abstract in cognition (Maynard, Greenfield, & Childs, 2015), have more subjectivist epistemic thinking (Weinstock, 2015), display more competitive and less cooperative behaviours (Garcia, Rivera, & Greenfield, 2015), express more equalitarian gender-related attitudes (Manago, 2015), perform fewer caregiver grooming behaviours (Thein, 2015) and hold more individualistic values (Zeng & Greenfield, 2015). In some of the studies, the researchers examined the links between the sociodemographic features as suggested by Greenfield (2009) (e.g., engagement in commercial activities, schooling, use of mobile technology, level of urbanisation) and child and youth performance.…”
mentioning
confidence: 99%